Urban Spaces and Safety - De Paoli, Rosa Grazia (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The concept of vulnerability understood in the traditional sense as a “single manufactured good” is insufficient when it comes to describing the real conditions of an urban system’s vulnerability within which an indefinite variable of factors interact with one another thereby determining the damage caused by an earthquake. These interacting factors constitute so-called “urban vulnerability” which town planners use in order to contribute to the field in the form of analysis definition and interventions in the mitigation of seismic risk on an urban scale. The research paper “Relational Spaces as Safe Places” positions itself firmly in the vein of town planning research which focuses on the mitigation of seismic risk, and which intends to blaze a new methodological trail that aims to identify safety traits in urban spaces. The research paper’s starting point is the assumption that empty urban spaces, given the indications provided by the principal organs for Civic Protection, have come to be seen as the spaces designed to accommodate the public in cases of emergency. This can generate new thought regarding town planning by reviewing early post-earthquake urban designs where the rules were laid out for earthquake-proof cities: a “chessboard” plan with wide streets, both straight and perpendicular, empty spaces like squares and markets positioned along the longitudinal streets, and buildings with regular layouts all at right-angles. These simple guidelines, which are often disregarded and distorted in modern towns, are extraordinarily relevant and oriented towards new definitions of the urban traits of quality and security.